Potentials of smart antennas in CDMA systems and uplink improvements. - Zooghby, Ahmed EL (IEEE Antennas & propagation magazine.)
An overview of the application of smart antennas in DS-CDMA systems, including IS-95 and IS-2000, is presented. Since CDMA systems are interference-limited, adaptive antenna arrays have great potential for improving the performance of such systems in terms of capacity, coverage, and quality of service, In this paper, we study the multiple-access interference that affects a CDMA system, and we describe how smart antennas can be implemented in an IS-2000-based mobile communications system. When smart antennas are used at the base station to transmit in narrow beams, the interference on the downlink is reduced, and C/I is improved. This, in turn, increases the system capacity on the downlink or, alternatively, the quality of service is improved. Such gains will prove very beneficial for asymmetric high-speed data applications, requiring much higher bit rates on the downlink than on the uplink. By reducing the base-station receiver's sensitivity, smart antennas can boost the capacity of the reverse link. Results are presented that outline how this reduction can be employed by the system designer on the uplink to increase capacity, reduce the mobile transmit power, or effect a tradeoff between capacity improvement and coverage or range extension under different system-loading scenarios.